Menumbuhkan Jiwa Entrepreneur Mahasiswa PPKN Melalui Mata Kuliah Kewirausahaan - NENENG RIKA JAZILATUL KHOLIDAH (Journal Civics and Social Studies, 2020)
AbstractThe increase of bachelor graduates will increase competition in looking for work  and the lack of  jobs will increase the number of  unemployment lists. Being unemployed is undesirable  because of self-harm and unbeneficial to the surrounding community. This study was aimed to determine the importance of entrepreneurship courses for students in the civics study program. This study used a qualitative method. The data collection techniques were observation, interview, and documentation. The informants were 25 students who have taken entrepreneurship courses. The results showed that the existence of entrepreneurship courses in higher education can foster entrepreneurial spirit by instilling knowledge and interest in entrepreneurship, fostering confidence and skills in entrepreneurship, increasing motivation to become young entrepreneurs. Keywords: Students, civics, entrepreneurship